Tweeting #humanwaste: A practical theological tracing of #humanwaste as a trend on Twitter - Van den Berg, J. A. (HTS teologiese studies, 2014)
Different and divergent facets of human existence are increasingly becoming embodied within a digital domain. The social media platform, Twitter, comprises an important expression of the digital world and social media, but also of popular culture. In a practical theological tracing of the theme of human waste on Twitter, new contents and meaning related to this concept are mapped out in a variety of categories. On the basis of existing and newly developed research methodologies, an exploration is conducted in order to indicate how the digital world can assist in the creation of new empirical realities, hermeneutic outcomes and strategic involvement. In this tracing of human waste as a theme on Twitter,accents of a possible lived spirituality are sounded out and verbalised. It is on the basis of these descriptions that possibilities unfold for new practical theological orientations, both for the present and the future.